Understanding Psychological Symptoms of Endometriosis from a Research Domain Criteria Perspective - van Stein, Katharina; Schubert, Kathrin; Ditzen, Beate; Weise, Cornelia (Journal of Clinical Medicine, 2023)
Endometriosis is currently the second most common gynecological disease and is associated with severe pain, vegetative impairment, and infertility. In association, there are considerable psychological symptoms that limit the quality of life of those affected. In this narrative review, the Research Domain Criteria (RDoC) framework was utilized to display the different transdiagnostic processes involved in disease progression and maintenance in regard to psychosocial functioning. Using the RDoC framework, it becomes clear that immune/endocrinological dysregulation is interlocked with (pelvic) pain chronification processes and psychological symptoms such as depressive mood, loss of control, higher vigilance toward the onset or worsening of symptoms, social isolation, and catastrophizing. This paper will discuss and identify promising treatment approaches, in addition to medical care, as well as further research implications. Endometriosis can come with substantial psychosomatic and social burden, requiring more research to understand the interdependence of different factors involved in its chronic development pathway. However, it is already clear that standard care should be extended with multifaceted treatments addressing pain, as well as the psychological and social burden, in order to halt the cycle of aggravation of symptoms and to improve quality of life for patients.
CRIS-Team Scopus Importer:2024-03-27
Keywords: endometriosis; infertility; pelvic pain; RDoC; stress-related diseases; women’s health